Imperial Russian Military Historical Society: to historiography of the problem - A. S. Shestopalova (Омский научный вестник: Серия "Общество. История. Современность")
The article is one of the first attempts to generalize the accumulated experience in the research literature on the history of the Imperial Russian Military Historical Society. The author analyzed the key works of pre-revolutionary, Soviet, postSoviet historiography. The presented historiographic review is built according to the chronological principle. The author comes to the conclusion that the first attempts to comprehend the activities of the Imperial Russian Military Historical Society were carried out even before the revolution of 1917, but only from the 1940s. laid the foundation for studying its history. It is concluded that the interest of modern researchers is fragmentary and is more focused on studying the activities of local departments and the organizational structure of society. A promising direction for further research is the study of the history of this association of military historians in the context of the interdisciplinary paradigm «Memory studies», which allows us to consider the Imperial Russian Military Historical Society as one of the most important actors influencing the formation of historical memory at the beginning of the 20th century.